The potential effect of HBV vaccination on off-treatment HBsAg reversion after interferon-induced HBsAg clearance - Shaowen Jiang; Minghao Cai; Zhenglan Zhang; Cong Qian; Jiexiao Wang; Ziqiang Li; Qing Guo; Huijuan Zhou; Haiguang Xin; Wei Cai; Hui Wang; Simin Guo; et al. (Taylor & Francis Group, 2023)
Off-treatment HBsAg reversion occurs in a considerable number of chronic hepatitis B(CHB) patients after IFN(interferon)-induced HBsAg clearance. HBV vaccination protects the general population against HBV infection. However, it remains unclear whether HBV vaccination could prevent off-treatment HBsAg reversion in CHB patients with HBsAg clearance. CHB patients (n = 199) with HBsAg clearance were included in the current study, comprising spontaneous HBsAg clearance group (n = 51), NA (nucleoside/nucleotide analogues)-induced group (n = 36) and IFN-induced group (n = 112). Log-rank test was performed to compare the cumulative incidences of HBsAg reversion between groups. Cox regression model was used to identify the factors associated with off-treatment HBsAg reversion. The 5-year cumulative incidence of HBsAg reversion in IFN-induced group was significantly higher than that in NA-induced group or spontaneous group (27.6% vs. 3.3% vs. 8.1%, both p < .05). In IFN-induced group, 66.7% of CHB patients received HBV vaccination. The cumulative incidence of HBsAg reversion in individuals with strong responses to HBV vaccination (HBsAb level >100mIU/ml) was significantly lower than that in those with weak responses to HBV vaccination (HBsAb level ≤100mIU/ml) or without HBV vaccination in IFN-induced group (7.7% vs. 58.5% vs. 31.9%, both p < .05). Multivariate Cox regression analysis confirmed strong responses to HBV vaccination were independently associated with a lower cumulative incidence of HBsAg reversion after IFN-induced HBsAg clearance (HR = 0.246, 95%CI: 0.066-0.907, p = .035). HBV vaccination has potential to prevent off-treatment HBsAg reversion in CHB patients after IFN-induced HBsAg clearance via a sufficiently high level of HBsAb, helping clinicians optimize the clinical management of such patients.